G-quartet oligonucleotide mediated delivery of functional X-linked inhibitor of apoptosis protein into retinal cells following intravitreal injection. (October 2018) - Talreja, Deepa; Cashman, Siobhan M.; Dasari, Bhanu; Kumar, Binit; Kumar-Singh, Rajendra
Abstract: There is currently no efficient method available for the delivery of full length functional proteins into the cytoplasm of retinal cells in vivo . Historically, the most successful approach for the treatment of retinal diseases has been intravitreal injection of antibodies or recombinant proteins, but this approach is not yet utilized for the delivery of proteins that require intra cellular access for a therapeutic effect. Here we describe a platform for the delivery of functional proteins into ganglion cells, photoreceptors and retinal pigment epithelium via intravitreal injection. A nucleolin binding aptamer, AS1411, was biotinylated and complexed with traptavidin and utilized as a platform for the delivery of GFP or X-linked inhibitor of apoptosis (XIAP) proteins by intravitreal injection in BALB/c mice. Retinal sections were analyzed for uptake of proteins in the retina. Apoptosis was induced by intravitreal injection of N -methyl-D-aspartate (NMDA). Retinas were harvested for analysis of TUNEL and caspase 3/7 activity. Intravitreal injection of AS1411-directed GFP or XIAP complexes enabled delivery of these proteins into ganglion cells, photoreceptors and retinal pigment epithelium in vivo . AS1411-XIAP complexes conferred significant protection to cells in the outer and inner nuclear layers following NMDA induced apoptosis. A concomitant decrease in activity of Caspase 3/7 was observed in eyes injected with the AS1411-XIAP complex. In conclusion, AS1411 can be used as a platform for the delivery of therapeutic proteins into retinal cells. This approach can potentially be utilized to introduce a large variety of therapeutically relevant proteins that are previously well characterized to maintain the structural integrity and function of retina, thus, preventing vision loss due to ocular trauma or inherited retinal degeneration. Highlights: A platform technology for aptamer mediated delivery of proteins into retinal cells in vivo following intravitreal injection. G-quartet aptamer mediated delivery of XIAP in vivo inhibits NMDA induced apoptosis in the retina. G-quartet aptamer mediated delivery of XIAP in vivo attenuates activation of Caspase-3.